OVERVIEW OF IRRIGATED AGRICULTURE EVOLUTION IN SOUTHEASTERN BRAZIL BETWEEN 2006 AND 2017 - Silva, César De Oliveira Ferreira [UNESP]; Putti, Fernando Ferrari [UNESP]; Manzione, Rodrigo Lilla [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
This research aimed to contribute to the debate about the current situation of irrigation in Brazil, with emphasis on the Southeast region. Based on data from the IBGE Agricultural Censuses of 2006 and 2017, we aimed to understand which directions irrigated agriculture has taken in Southeastern Brazil during this period. There was an increase in the irrigated area in Brazil in all geographical regions, reaching 6.9 million hectares (Mha) in 2017. In the period 2006-17, the expansion of the irrigated area in the state of Minas Gerais was 616,000 hectares, in São Paulo it was 321,000 hectares and 155,000 hectares in Espírito Santo. In the Southeast region, drip irrigation is the majority in the area, with 25% of the area irrigated, followed by sprinkler irrigation (24%) and central pivot (23%). The irrigated area in the Southeast region, according to the 2017 Census, is mostly for temporary crops (48%), permanent crops (29%), horticulture and floriculture (14%), and livestock (10%). These information are important for planning the sustainable expansion of irrigated agriculture and efficient water use.
PANORAMA DA EVOLUÇÃO DA AGRICULTURA IRRIGADA NO SUDESTE DO BRASIL ENTRE 2006 E 2017
Keywords: Census of agriculture; Irrigated area; Irrigation methods